In Order to Live a North Korean Girl's Journey to Freedom - Park, Yeonmi (New York Penguin Press, 2015)
Yeonmi Park has told the harrowing story of her escape from North Korea as a child many times, but never before has she revealed the most intimate and devastating details of the repressive society she was raised in and the enormous price she paid to escape.
Keywords: Park, Yeonmi, 1993-